Experience with local negative pressure (vacuum method) in the treatment of complex wounds - Wada, Alexandre; Ferreira, Marcus Castro; Tuma Júnior, Paulo; Arrunátegui, Gino (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Use of topical nega- tive pressure over difﬁcult-to-heal wounds has been studied. The objective of this study was to analyze the effects from negative pressure in the treatment of complex wounds. DESIGN AND SETTING: Case series developed at Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo. METHODS: Twenty-nine patients with complex wounds were treated with the vacuum system and then underwent a surgical procedure to close the wound. RESULTS: 85% of the skin grafts took well, and 87.5% of the local ﬂaps were successful, thus demonstrating adequate wound preparation. The wounds were closed within shorter times than observed using other conventional treatments In two cases, the vacuum system was also used to stabilize the skin grafts over the wounds. CONCLUSIONS: Use of the vacuum method is safe and efﬁcient for preparing wounds for surgi- cal closure. It allows for an improvement of local wound conditions, and healthy granulation tissue develops with control over local infection.